Evaluasi Atas Pelaksanaan Audit Dalam Meningkatkan Efektifitas Sistem Informasi Persediaan Barang Jadi : Studi Kasus Pada PT. Cahaya Furnindotama - Djanegara, H. Moermahadi Soerja (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2004)
This research was carried out to gain a picture, how far internal audit in increasing the information system of finished product stock conducted by the firm. The finished product stock consistsof various different goods, it defends on the nature of business activity. In case of stock control, the firm has to possess trustworthy system and procedure so that being able to increase internal control system effectiveness which is related to stock management. From the analysis result, it can be seen that there are numerous shortagesin internal audit, espectially in raising control system effectiveness of stock of finished product at PT Cahaya Furnindotama. Key Words : Auditing; Information system of supplies